The Influence Of Satisfaction And Trust On Consumer Loyalty In Medan Oranges In Medan City Compared To Imported Oranges - Hasibuan, Iqbal Fairuz; Netti Tinaprilla; Joko Purwono (Journal of Agri Socio Economics and Business, 2023)
People's lifestyles are changing to meet their needs, and they are increasingly shopping at modern retailers. For Indonesian consumers, the presence of modern retail businesses such as minimarkets, supermarkets and even hypermarkets is very encouraging. Consumers are pampered with various positive things related to shopping convenience, safety, comfort, increasingly diverse product variations, increased product quality, and of course cheaper product prices due to competition. This research aims to test the influence of all aspects of the marketing mix on loyalty through satisfaction and trust The research uses a quantitative approach with an exploratory approach, the analysis method used is the SEM analysis method with Smart PLS. Based on the research results, it was found that only price influenced satisfaction. satisfaction and trust have a significant influence on loyalty. Furthermore, satisfaction is able to mediate price on loyalty.